VANET and its Security Issues- A Review - Singh, Varinderjit; Mahajan, Karan (International Journal of Computer Sciences and Engineering, 2025)
Vehicular Adhoc Networks (VANETs) are gaining growing interest and research efforts over recent years for it offers enhanced safety and enriched travel comfort. However, security concerns that are either general seen in adhoc networks or unique to VANET present great challenges. This review paper presents the basics of VANET which includes architecture of VANET, its applications and its characteristics. The major consideration of this paper is on security, so security requirements and issues related to security are also presented in this paper. This paper also provides information about types of attackers and types of attacks in VANET.